2010
DOI: 10.4097/kjae.2010.58.4.378
|View full text |Cite
|
Sign up to set email alerts
|

Propofol has delayed myocardial protective effects after a regional ischemia/reperfusion injury in an in vivo rat heart model

Abstract: BackgroundIt is well known that propofol protects myocardium against myocardial ischemia/reperfusion injury in the rat heart model. The aim of this study was to investigate whether propofol provides a protective effect against a regional myocardial ischemia/reperfusion injury in an in vivo rat heart model after 48 h of reperfusion.MethodsRats were subjected to 25 min of left coronary artery occlusion followed by 48 h of reperfusion. The sham group received profopol without ischemic injury. The control group re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
11
0
1
Order By: Relevance
“…Numerous anesthetics are used for cancer surgery, such as propofol, remifentanil and sevoflurane (26,27); however, their effects on the potential behaviors of cancer remain unknown. Propofol is an anesthetic agent that exerts numerous anesthetic, neuroprotective and myocardial-protective effects (18,28,29). Previous studies have demonstrated an association between propofol use and antitumor effects (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous anesthetics are used for cancer surgery, such as propofol, remifentanil and sevoflurane (26,27); however, their effects on the potential behaviors of cancer remain unknown. Propofol is an anesthetic agent that exerts numerous anesthetic, neuroprotective and myocardial-protective effects (18,28,29). Previous studies have demonstrated an association between propofol use and antitumor effects (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…The catheter was advanced into the left ventricle (LV) to measure the heart rate (HR), left ventricular systolic pressure (LVSP), left ventricular end diastolic pressure (LVEDP), the increase in the peak rate of intraventricular pressure increase (+dP/dtmax), and the decrease in the peak rate of intraventricular pressure (−dP/dtmax) [20]. …”
Section: Methodsmentioning
confidence: 99%
“…All animals were maintained in accordance with the Guidelines for the Care and Use of Laboratory Animals published by the US National Institutes of Health in 1996. Animal preparation and surgery were done according to previous report 13. Animals received general anesthesia with an intramuscular injection of 80 mg/kg ketamine (ketamine HCl®, Huons, Seoul, Korea) and 8 mg/kg zylazine (Rompun®, Bayer Korea, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%